Nghiên cứu tổng hợp và thăm dò hoạt tính sinh học của phức chất Neodim với L-methionin. - Uyển, Nguyễn Trọng; Thiềng, Lê Hữu; Điều, Trần Lương; Vân, Nguyễn Thuý (Vietnam Journal of Chemistry, 2012)
The complex of neodymium with L-methionin has been isolated from solid state. The structure of the complex was determined by thermal decomposition and IR spectral methods. At the concentration of from 30 ppm to 150 ppm, the complex has influence on stimulating sprout and cross-bred rice development, the stimulation is increased according to the concentration. And the stimulation level of complex is less than that of central ion ligand and gamete.